COVID 19 scoping: A systemic review and meta-analysis - Harisha Dewan; Mohammed Nishan; Shan Sainudeen; Sanskriti; Kunal Jha; Ashish Mahobia; Rahul V C Tiwari (Wolters Kluwer Medknow Publications, 2021)
Introduction: The world has faced the pandemic of COVID-19 in the march of 2020 and still it continues to effect in 2021. Hence, in the present study we aim to evaluate the gulps in the research so that certain recommendations can be made for the future research. We conducted a scoping review of the COVID meta-analysis. Materials and Methods: Online data was collected from the search engines of EBSCO, PubMed, Google Scholar, and Scopus. The searched terms were COVID-19, CORONA, SARS-CoV-2, clinical features, Wuhan, etc. The study articles were collected that from January 2020 to February 2021. Based on the PRISMA guidelines, the meta-analysis was performed. Results: In the present study, we finalized 316 articles. On February 2020, the first article was published. We observed a spike in the meta-analysis later on. Most of the meta-analysis were issued in the virology and infection magazines. As expected, the majority studies were from Wuhan. The other countries that published the meta-analysis were the USA, the UK, and Italy. The studies included in each meta-analysis were nearly 25 and the subjects were approximately 16 thousand. However, we noticed a poor quality in majority of these meta-analysis and <10% of all the meta-analysis showed higher confidence. Conclusion: A poor quality of the meta-analysis has predominated the data and very few are of high quality. All the journal editors and the reviewing team should verify and thoroughly organize the protocol so that only high quality meta-analysis are encouraged.